Oomycete Communities Associated with Reed Die-Back Syndrome - Cerri, Martina; Sapkota, Rumakanta; Coppi, Andrea; Ferri, Valentina; Foggi, Bruno; Gigante, Daniela; Lastrucci, Lorenzo; Selvaggi, Roberta; Venanzoni, Roberto; Nicolaisen, Mogens; Ferranti, Francesco; Reale, Lara (Frontiers in Plant Science, 2017)
Phragmites australis (Cav.) Trin. ex Steud. die-back is a widely-studied phenomenon that was first discovered in northern Europe and that, until recently, was almost unknown in the Mediterranean basin. It has been described as a complex syndrome affecting reed populations leading to their retreat and decline, with significant impacts on valuable ecosystem services. Among the factors that cause the decline, soil-living microorganisms can be crucial. The aims of this study were to analyse the diversity of oomycetes communities associated with reed stands, and to understand whether they could play a key role in the decline. Variations in the structure of oomycetes communities were studied by metabarcoding of the internal transcribed spacer (ITS) 1 region of ribosomal DNA, from the sediments of five Italian freshwater ecosystems. They were chosen to cover a large variability in terms of surface area, water depth, microclimate and presence of documented reed retreat. From 96 samples collected from reed roots, rhizosphere, and bulk soil, we assembled 207661 ITS1 reads into 523 OTUs. We demonstrated that oomycete communities were structured by several factors, among which the most important was die-back occurrence. Our study also indicates that Pythiogeton spp. could be potentially involved in the development of die-back. The role of heavy metals in the soil was also explored, and cadmium concentration was shown to affect oomycetes distribution. This study represents a significant step forward for the characterization of microbial communities associated with reed die-back syndrome and helps to gain knowledge of the complexity of these important wet ecosystems.